Parâmetros para identificação dos estágios de desenvolvimento das cidades inteligentes no Brasil - Hiroki, Stella Marina Yurí (2019)
As from the eighties, there is a change of paradigms of city management to a corporate model; the planning framework of the urban spaces is amended whilst private initiatives identified investment potential in the cities. Together with this background, the arrival of new Information and Communication Technologies (ICTs) and ever-increasing use of the Internet at the turn of the twentieth first century have contributed with a view for efficiency in the urban space. Added to these factors, global challenges such as high population density, a more conscientious use of natural resources and the pursuit of innovation, efficiency and improved visibility in the urban spaces have driven for implementing the concept of Smart City. With this outlook, this thesis is seeking to set parameters that enable detecting the development stages of the Smart Cities in Brazil. Underpinned by a bibliographic review, this assignment describes an international panorama over the implementation of Smart City as well as the course of the directions in Brazil which has led to the evolution of this concept in the country. It is evaluated that in the Brazilian context there is a consolidation of the studies and it is pointed out to the critical remarks with regarding to the subject in the country highlighting the concern in relation to the social challenges that Brazil presents. In this sense, it is identified that the interest in starting off the implementation of a new urban management in the country, which allowed the city to be competitive at international level, occurred still in the nineties in Curitiba by the adoption of “city marketing”. For this reason, assessment tools from the private initiative began to be used to grade performance of the cities, such as benchmarking and indicators. Thus, drawing on the analysis of three examples of the Smart Cities rankings: European Medium-Sized Cities, Connected Smart Cities and IESE Cities in Motion, this assignment endorses that the current forms of evaluation to grade cities as Smart do not fit into the Brazilian reality. Following, this assignment is supported by researches carried out in cities graded as Smart Cities and also in lab tests on the subject, such as SMU University in Singapore (2015) and The Programmable City Lab in Maynooth University Dublin, Ireland (2017) referring projects which have worked to consolidate the concept of Smart Cities in these cities. Thereby, this assignment indicates 53 parameters divided into four axes: Governance, Social Cohesion, Technology and International Indicators which are also specified in accordance to the motion in its application in the city, that is, a top down motion, bottom up and a joint motion that allow the identification of the implementation stages of Smart Cities in Brazil. In the sequence, these parameters are applied at three cities: Rio de Janeiro, São Paulo and Curitiba. It can be observed that there are significant practices in the country which could be worldwide references in the application of the concept of Smart Cities, on the other hand, there is also a wide field to be developed